1989
DOI: 10.1139/g89-139
|View full text |Cite
|
Sign up to set email alerts
|

Molecular population genetics of structural variants of esterase 6 in Drosophila melanogaster

Abstract: Several lines of evidence indicate that natural selection operates between the major EST6-F and EST6-S allozymes of Drosophila melanogaster. In particular, consistent latitudinal clines and seasonal variation in their relative frequencies strongly suggest that they are not selectively equivalent in field populations. Several laboratory studies have found frequency-dependent fitness differences among the Est6-F and Est6-S genotypes. Moreover, the purified EST6-F and EST6-S allozymes differ in biochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The present analysis of the Est-6 coding region confirms our previous suggestion that the pattern of nucleotide variability of the Est-6 coding region is shaped by the influence of both directional and balancing selection (Balakirev et al, 1999; see also Oakeshott et al, 1989Oakeshott et al, , 1993Oakeshott et al, , 1995Richmond et al, 1990). Window analysis of DNA sequence variation reveals an excess of polymorphism surrounding the site that determines the F/S allozyme polymorphism (Fig.…”
Section: Polymorphism At the Esterase-6 (Est-6 ) Locussupporting
confidence: 90%
See 1 more Smart Citation
“…The present analysis of the Est-6 coding region confirms our previous suggestion that the pattern of nucleotide variability of the Est-6 coding region is shaped by the influence of both directional and balancing selection (Balakirev et al, 1999; see also Oakeshott et al, 1989Oakeshott et al, , 1993Oakeshott et al, , 1995Richmond et al, 1990). Window analysis of DNA sequence variation reveals an excess of polymorphism surrounding the site that determines the F/S allozyme polymorphism (Fig.…”
Section: Polymorphism At the Esterase-6 (Est-6 ) Locussupporting
confidence: 90%
“…This and results from laboratory experiments suggests that the EST-6 polymorphism is maintained by some form of selection (reviewed by Oakeshott et al, 1989Oakeshott et al, , 1993Oakeshott et al, , 1995Richmond et al, 1990). Cooke and Oakeshott (1989) suggested that the main Fast and Slow allozymes differ by two amino acids (Asn/Asp at position 237 and Thr/Ala at position 247) (but see Hasson and Eanes, 1996;Balakirev et al, 1999) and that these two amino acid polymorphisms are the most likely targets for selection underlying the latitudinal clines (Oakeshott et al, 1981).…”
Section: Polymorphism At the Esterase-6 (Est-6 ) Locusmentioning
confidence: 99%
“…This variation is cryptic to the standard electrophoretic procedures used to describe the clines but can be detected by thermostability analyses or higher resolution electrophoresis (Cochrane & Richmond, 1979;Cooke, Richmond & Oakeshott, 1987). In D. melanogaster there are several relatively common variants within EST6-F but one form, denoted EST6-8, dominates in frequency within EST-S in all populations investigated (Labate et al, 1989). In D. simulans several variants have been reported within both EST6-F and EST6-S but none of them correspond to EST6-8 (Albuquerque & Napp, 1981;Karotam, Boyce & Oakeshott, in press).…”
Section: Polymorphisms Within D Melanogaster and D Simulansmentioning
confidence: 99%
“…Thus the sequencing of multiple isolates of the Est6 coding region reveals multiple amino acid polymorphisms segregating both within and between the major EST6-F and EST6-S allozymes . Some, but not all, of these amino acid differences correspond to minor mobility variants detectable by higher resolution electrophoretic procedures, or to other variants detectable by-thermostability criteria Oakeshott et al, 1989). Furthermore, most of the EST6 enzyme activity variation among field derived lines is not due to structural differences in the enzyme but to differences in its amount, and these differences are associated with restriction fragment length polymorphisms (RFLPs) in the Est6 promoter Ludwig, Tamarina & Richmond, 1993).…”
Section: Introductionmentioning
confidence: 99%